Analisis Dampak Revitalisasi Jalan Tunjungan terhadap Pendapatan dan Perkembangan UMKM di Wilayah Jalan Tunjungan Surabaya - Kusumatuti, Berlian Sukma (OECONOMICUS Journal of Economics, 2024)
This research is about the impact on income and development of MSMEs in the Jalan Tunjungan Surabaya area. Jalan Tunjungan itself is a historical area that was founded in 1950 and is located in the center of Surabaya. The aim of this research is to determine the impact on income and development of MSMEs in the area after and after revitalization. Therefore, this research will examine in more depth the income and development of MSMEs. This research uses a descriptive method with a qualitative approach. The types of data used are primary and secondary data. Primary data was obtained from observations and interviews. Secondary data was obtained from official government websites, previous research journals and others. In this research, there are several obstacles such as inadequate facilities on Jalan Tunjungan, low income levels and the development of MSMEs before the revitalization process